Coiled Tube Turbodrilling: a proposed technology to optimise drilling deep hard rocks for mineral exploration. (2013) - Mokaramian, Amir; Rasouli, Vamegh; Cavanough, Gary
The need to drill deep boreholes more efficiently for mineral exploration has raised the attention to investigate the feasibility of recent drilling technologies for such applications. The two principal methods of Reverse Circulation (RC) and diamond core drilling are usually used in combination by mine operators are subjected to certain limitations and inefficiencies. Considering that delivering large volume of reliable samples from deep zones to the surface in shortest possible time is of paramount importance in mineral exploration, then drilling small size holes as fast as possible and delivering the small chip samples to the surface would be a good alternative with several advantages over conventional drilling methods. As a result, the Coiled Tube (CT) turbodrilling technology is proposed here followed by presenting detailed calculations for the system required power and hydraulics and also Bottom Hole Assembly (BHA) selection suitable for hard rocks mineral exploration applications.